Pembelajaran Blended Learning pada Materi Laju Reaksi dan Dampaknya Terhadap Hasil Belajar - Aulyah, Azizah; Purwoko, Agus Abhi; Supriadi, Supriadi (Chemistry Education Practice, 2024)
This research aims to determine the effect of learning outcomes of class XI IPA students at SMA Negeri 2 Mataram by using blended learning on the subject matter of reaction rates. An understanding of abstract chemical concepts requires appropriate learning strategies so that in the learning process students do not feel bored. The use of blended learning by paying attention to students initial abilities is thought to be able to overcome this problem. This type of research is a quasi-experimental research. The research data used a learning achievement test which consisted of 13 multiple choice questions accompanied by reasons. The results showed that the average learning outcomes of students who were taught using blended learning were higher then those who were taught using conventional learning. Data analysis used a One-way Ancova statistical test, and after being tested, the results showed that blended learning did not have a significant effect on the chemistry learning outcomes of class XI IPA students at SMA Negeri 2 Mataram.